2017
DOI: 10.1037/adb0000312
|View full text |Cite
|
Sign up to set email alerts
|

The Angel and the Devil on your shoulder: Friends mitigate and exacerbate 21st birthday alcohol-related consequences.

Abstract: Twenty-first birthdays are associated with heavier drinking and more negative consequences than any other high-risk drinking event. Friends are the strongest social influence on young adult drinking; however, previous research on college students’ drinking has often only examined individuals’ perceptions of “friends” generally. Unfortunately, this may obscure the positive influence of some friends and the negative influence of others. Using data drawn from a larger intervention study aimed at reducing 21st bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Students experience more harm, independent of increased consumption, when they drink in larger groups and mixed sex rather than same‐sex pre‐drinking settings . The type of company is generally not a significant predictor, although having close friends who intend to encourage the celebrant to drink alcohol at 21st birthday events (the legal drinking age in the US) is linked to increased harm .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students experience more harm, independent of increased consumption, when they drink in larger groups and mixed sex rather than same‐sex pre‐drinking settings . The type of company is generally not a significant predictor, although having close friends who intend to encourage the celebrant to drink alcohol at 21st birthday events (the legal drinking age in the US) is linked to increased harm .…”
Section: Resultsmentioning
confidence: 99%
“…Aggregate measures of multiple acute harms are the most commonly studied outcome ( n = 30; 32%). These are usually based on a checklist of harms, sometimes adapted from validated scales such as the Young Adult Alcohol Problems Screening Test . Most of these papers study student ( n = 25; 83%) or US ( n = 24; 80%) populations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the drinking motivation measures used are not based on a standard validated survey tool such as the Drinking Motives Questionnaire. There were also no measures of drinking companions’ behavior, drinkers’ expectancies, or drinkers’ intentions, which previous studies have linked to consumption in drinking occasions (Fillo et al, 2017; Larsen et al, 2009; Monk and Heim, 2013; Stevens et al, 2017). Furthermore, we have not analyzed factors that are associated with having a drinking occasion in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…companions' behavior, drinkers' expectancies, or drinkers' intentions, which previous studies have linked to consumption in drinking occasions (Fillo et al, 2017;Larsen et al, 2009;Monk and Heim, 2013;Stevens et al, 2017). Furthermore, we have not analyzed factors that are associated with having a drinking occasion in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, drinking in pubs has been associated with violence . In the US college literature, themed parties were associated with increased blood alcohol concentration , and friends’ high safety intentions for 21st birthday celebrations reduced the likelihood of negative alcohol‐related consequences . Researchers in Switzerland and Australia also found that pre‐drinking, drinking with a greater number of friends and drinking in a mixed‐gender group are all associated with increased alcohol consumption during an occasion .…”
Section: Introductionmentioning
confidence: 98%